Human Endometrial Stromal/Stem Cells Inhibit Apoptosis in Cisplatin-Induced Acute Kidney Injury in Male Wistar Rats - Hadis Zeinali (Royan Institute (ACECR), Tehran, 2021)
stromal/stem cells (hEnSCs) are mesenchymal stem cell (MSC)-like cells, which are suitable candidates for regenerative medicine purposes, yet the effect of hEnSCs on cisplatin-induced AKI has not been studied; therefore, the present study was conducted to investigate this gap in the literature. Materials and Methods: In this experimental study, hEnSCs were obtained from endometrial biopsy using collagenase I and were then cultured in DMEM/F12 medium. A total of 48 male Wistar rats (150-200 g) were classified into four groups: intact -receiving no treatment, model -receiving 5 mg/kg of body weight cisplatin, as well as phosphate-buffered saline (PBS) and cell -receiving either PBS or hEnSCs for three hours after cisplatin injection, respectively. Biochemical parameters, pathologic scores, apoptosis assay, Bcl-2 and Tnf-α expression were evaluated on day 5. Results: On day 5 post-transplantation we observed that HEnSCs injection has led to a decrease in both blood urea nitrogen (BUN) and serum creatinine (SCr), compared to the model and PBS groups (0.82 ± 0.03 vs. 1.42 ± 0.06, 1.09 ± 0.05 mg/dl and 61.53 ± 3.07 vs. 116.60 ± 2.12, 112.00 ± 1.35 mg/dl, respectively). The highest levels of pathologic scores were observed in model and PBS groups, while hEnSCs transplantation resulted in a decrease in pathologic scores (149.10 ± 7.03, 141.50 ± 4.68 vs. 118 ± 2.16). HEnSCs significantly decreased the percentage of TUNELpositive cells in the cell group compared with model and PBS groups (20.37 ±. 3.37 vs. 33.67 ± 1.79, 31.53 ± 1.05 in glomeruli and 15.10 ± 1.47 vs. 42.33 ± 1.72, 39.23 ± 1.61 in tubules). In addition, HEnSCs resulted in upregulation of Bcl-2 and downregulation of Tnf-α in the cisplatin-induced AKI. Conclusion: Our results showed that injection of hEnSCs may improve AKI through lowering the amount of apoptosis in renal cells.